2018
DOI: 10.20944/preprints201808.0387.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FTIR Spectroscopy of the Regulated Asbestos Amphiboles

Abstract: Vibrational spectroscopies (FTIR, Raman) are exceptionally valuable tools for the identification and crystal-chemical study of fibrous minerals, and asbestos amphiboles in particular. Raman spectroscopy has been widely applied in toxicological studies and thus a large corpus of reference data on regulated species is found in the literature. However, FTIR spectroscopy has been mostly used in crystal-chemical studies and very few data are found on asbestos amphiboles. This paper is intended to fill this gap; we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
(107 reference statements)
2
6
0
Order By: Relevance
“…The XRPD pattern collected for the studied sample could be fully indexed in the C 2/ m space group. Refined cell dimensions were (in Å): a = 9.832 (1), b = 18.065 (4), c = 5.273 (1), β (°) = 104.76 (2), V (Å 3 ) = 905.7 (2), consistent with literature data for amphiboles in the tremolite-actinolite series, see [23]. The XRPD pattern further revealed the presence of a very small amount of chlorite (2 wt.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The XRPD pattern collected for the studied sample could be fully indexed in the C 2/ m space group. Refined cell dimensions were (in Å): a = 9.832 (1), b = 18.065 (4), c = 5.273 (1), β (°) = 104.76 (2), V (Å 3 ) = 905.7 (2), consistent with literature data for amphiboles in the tremolite-actinolite series, see [23]. The XRPD pattern further revealed the presence of a very small amount of chlorite (2 wt.…”
Section: Resultssupporting
confidence: 81%
“…The powder FTIR spectrum collected in the OH-stretching region (Figure 5a) shows three well-resolved components at 3672, 3659 and 3643 cm −1 , which can be assigned to different combinations of Mg and Fe 2+ at the M (1,3) sites of the amphibole structure [23,32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 and Figure 4 show representative FTIR ATR spectra collected on powdered fragments of the shards. Spectrum d f has been recorded on a fiber bundle extracted from sample d. The bands, for instance, the Si-O stretching and bending modes at ~960 (1015 and 1080) and 620 cm −1 ( Figure 3 ), are characteristic of asbestos and similar compounds (amphiboles and pyroxenes) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. From this first analysis, it can be seen that the samples b and d on the one hand and the samples a and c on the other hand are rather similar, but sample d appears to be more heterogeneous.…”
Section: Resultsmentioning
confidence: 99%
“…The large number of phases identified by XRPD and the variety of Raman spectra observed are consistent with a firing taking place at low temperature, with a resultant degradation of the pristine mineral occurring without the clear formation of neophases. Trittschack et al [ 18 , 19 , 20 ] observed the intensity decrease of the O-H stretching mode at ~3600–3700 cm −1 over 450 °C (de-hydroxylation) and then the formation of forsterite at a temperature over ~500 °C, with the characteristic doublet seen at ~820–850 cm −1 .…”
Section: Resultsmentioning
confidence: 99%